River dynamics in the cordillera oriental of the andes (northwestern argentina) - Cencetti, Corrado (Italian journal of engineering geology and environment, 2008)
The paper describes the river dynamics and slope dynamics processes taking place in the section of the Andes in northwestern Argentina (Cordillera Oriental Unit), analyzing the causes in terms of agents, factors and conditions.The rising of this area of the chain is at the basis of the erosion and debris flow phenomena found there, which are favored both by climatic conditions (subarid, with little precipitation that is concentrated in infrequent but intense rains) and by the presence of clastic Quaternary rocks - the sedimentation of which is the fruit of wetter periods than the present - which are easily degradable and remobilizable by the present channel net.Consequently intense solid transport and alluviation phenomena are produced in the river channels, which are generally of the braided type. These take place by means of debris flows that, when triggered along the slopes, feed large alluvial fans that invade the main river channels.The geomorphological processes taking place in the region (which generate unusual morphotypes, such as terraced telescopic fans) can be considered the result of two apparently contrasting processes: on the one hand, vertical erosion and the general deepening of the channel net due to rising; on the other, the tendency toward alluviation, due to the mobilization of the clastic material from valley slopes through debris flow processes.The result should be considered as the expression of the delicate equilibrium between tectonic factors and climatic conditions: when the rate of rising (and thus of the cutting of the channel net) prevails over the contribution of debris from the slopes (depending on wetter or drier climatic conditions), there is erosion in the channel; vice versa (and this seems to be the overall condition at the time), when the contribution of debris from the slopes is abundant compared to the rivers' capacity to carry off the solid transport and compared to the linear erosion due to rising, the tendency is toward the aggradation of the river channels, which brings about evident conditions of geologic-hydraulic risk due to flooding.The Quebrada de Humahuaca (Upper Valley of the Rio Grande), in the Jujuy province, is an excellent example of the phenomena just described on the particular and complex morphological dynamics of this area of the Andine Cordillera. In many cases, both the villages along the courses of the Rio Grande and its tributaries and the roads running through the main valley suffer from this situation, which pre-cludes, in the present state, the socioeconomic development of a region with enormous potentialities, thanks to its attractiveness to tourists.